Electric consumption and conservation of households in Marikina City - Canals, Lee Ann Uichanco; Gabriel, Florenda S. (2009.)
The study described the knowledge, attitudes and practices of households regarding electric conservation. Marikina City was chosen as the study area with cluster sampling as the sampling method used to select a sample size of 50 households. The head of the household answered a survey questionnaire developed by the researcher. The instrument included average electric consumption, a knowledge test, an attitude scale and a self-report of conservation practices of the households. Majority (60%) of the households consumed an average of 300 kWh per month with a per capita consumption of 65.4 kWh or roughly equivalent to Php581.00. They had fair knowledge in electricity and electric consumption of an appliance and identifying when to defrost a freezer. Respondents had a generally positive attitude towards electric conservation. Money savings in particular, was a motivation for conserving electricity. Respondents also had a positive attitude towards their responsibility to know more about electric conservation. However, the respondents felt that they had to be reminded to conserve electricity were generally frequently practiced. Turning off lights when leaving a room and turning off unnecessary lights were the most frequently practiced. On the other hand, turning computers off when it is not being used was the least frequently done energy conservation practice.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Energy consumption -- Philippines -- Marikina City; Energy conservation -- Philippines -- Marikina City